Diagnóstico imunoenzimático da larva migrans visceral - Schoenardie, Elizandra Roselaine (2005)
The Visceral Larva Migrans (VLM) is a zoonotic disease caused by the helminth Toxocara cannis. The precocious diagnosis of this disease in humans is very important to determinate the evolution of the clinical case and the patient's treatment. The goal of the first experiment was determinate the presence of antibodies anti-T. cannis in children from Pelotas through the Indirect Enzyme-Linked Immunosorbent Assay (ELISA) front to the antigen TES, as well as to define the pattern of bands recognized by the positive serums in ELISA through the "Western blotting . For this experiment 427 serums from children, with ages between one to eleven yeas old was tested, those serums was adsorved with AgSoAl and determinate that 50,6% was positive for antibodies anti-TES, showing a significant association among the positive children for antibodies anti-TES and the contact with dogs and cats. This association was also observed in the children's different age groups, but not regarding the gender of the same ones. To perform the Western Blotting , 70 serums witch give a positive result in the Indirect ELISA was been used, all serums recognize glicoproteic bands in the range between 30 and 120 kDa. Was observed a diminution in the crusade reaction with AgSoAl when the adsorved and not adsorved serums with this antigen has been test in the Western blotting , where a band of 30 kDa demonstrate to be an important glicoprotein to specific diagnosis of VLM. In the second experiment, 25 mice BALB/c were inoculated with approximately 1000 eggs containing the larvae L3. Each fifteen days blood collection was made through the reto orbital plexus until the 105 days after de animals infection. The serums was tested in the Indirect ELISA using the Antigen TES and urea 6M in order to discriminate recent and late infection, through the percentile of avidity of the IgG in the different days after the infection. A low percentile of avidity was observed to the 15 days after inoculation (between 7,25 and 27,5%). After 60 days of infection, all the animals presented avidity between 31,4 and 58%. This result suggests that in mice BALB/c, to the 60 days after infection the chronic phase of VLM is already established.